T4 endonuclease VII cleaves the crossover strands of Holliday junction analogs. - Mueller, J E (1988)
We have formed four-arm branched DNA junctions that contain no more than a single base pair of branch migratory freedom. Recently, we have shown that these Holliday junction analogs have twofold symmetric protection patterns in solution when probed with hydroxyl radicals: two opposite strands of one junction show extensive protection near the branch point, while the other pair of opposite strands is virtually as susceptible as a double helix. In a different junction, the hydroxyl radical protection pattern is reversed. These patterns suggest that a crossover-isomer bias exists in these molecules and that the protected strands form the crossover between helices. Here, we examine the cleavage pattern of these structures when they are resolved by T4 endonuclease VII. Junctions are formed from a single shamrock-shaped molecule, which contains 5', 3', or internal labels. The enzyme shows a preference for resolving these modified junctions at sites near those protected from hydroxyl radicals. This result suggests that only crossover strands in a Holliday junction are cleaved, and thus an odd number of crossover isomerizations must occur when flanking markers are exchanged.